New species and records of Neotropical Cardiocladius Kieffer, 1912 (Diptera: Chironomidae, Orthocladiinae). Issue 4 (1st October 2016) - Andersen, Trond; Hagenlund, Linn K.; Pinho, Luiz C.
ABSTRACT: Cardiocladius moreloensis sp. n. is described and figured based on adult males collected in Morelos State in Mexico. Males of C. brasiliensis Oliveira, 1949 and C. travassosi Oliveira, 1951 are redescribed and figured based on new material from São Paulo State in Brazil. The generic diagnosis is expanded, and a key to the males of the Neotropical Cardiocladius species is presented. http://zoobank.org/urn:lsid:zoobank.org:act:EE8B2267-3362-4A1F-BED6-0A1E35D7D480